PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB PADA MATERI PERAWATAN DAN PERBAIKAN JARINGAN NIRKABEL KELAS XI TKJT DI SMK NEGERI 4 SOLOK SELATAN - Sartika, Reni; Samudra, Ami Anggraini; Novita, Rini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to develop a valid and practical web-based interactive learning media using the ADDIE model. The study was conducted at SMK Negeri 4 Solok Selatan in Wireless Network Maintenance for grade XI TKJ. The main issue identified was low student engagement and difficulty understanding the material. Validation results showed media experts rated it 88.27% as "Highly Valid," and material experts rated it 87.41% as "Highly Valid." Practicality assessments by teachers reached 95.83% as "Highly Practical," while students rated it 81.03% as "Highly Practical." Thus, this learning media is valid and practical for classroom use.